2021
DOI: 10.1002/cnma.202100177
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Snowman‐shaped Photocatalytic Microrotors and Mechanical Micropumps

Abstract: We synthesize snowman‐shaped microrotors that are composed of TiO2 and SiO2 particles fused together and half‐coated with Au. The microrotors rotate in the presence of fuel and UV light and the rotation speed is readily modulated by the fuel concentration and the light intensity. Such a microrotor can be transformed into a mechanical micropump that hydrodynamically, rather than electrokinetically, pumps nearby fluids and particles, with a pump power that scales linearly with its rotation speed. This work there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…At the same time, molecules could be highly soluble in SC fluid. Therefore, the SC fluid is an environmentally friendly alternative to organic and aqueous solvents [30] . For instance, Liu et al.…”
Section: Construction Of Cofs‐based Inorganic/organic Composite Mater...mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, molecules could be highly soluble in SC fluid. Therefore, the SC fluid is an environmentally friendly alternative to organic and aqueous solvents [30] . For instance, Liu et al.…”
Section: Construction Of Cofs‐based Inorganic/organic Composite Mater...mentioning
confidence: 99%
“…Therefore, the SC fluid is an environmentally friendly alternative to organic and aqueous solvents. [30] For instance, Liu et al first reported a close-connected TiO 2 /COFs composite material prepared by the supercritical CO 2 (SC CO 2 ) method. [31] COFs (TbBd) were dispersed in ethanol containing tetrabutyl titanate (TBT), and the compressed CO 2 was then pumped into the reactor with a small amount of water (5.52 MPa).…”
Section: Covalent Bonded Composite Materialsmentioning
confidence: 99%
“…12−15 For example, by electrochemical deposition, a gold layer is half-coated on twinned microrods or snowman-shaped particles and both the geometric and chemical symmetries are broken. 14,16 This thereby can lead to well-controlled and interesting self-rotational motions of the micromotors, which facilities many practical applications, such as cargo delivery and micropumping. 14,16 Although such a deposition method has been used to fabricate micromotors, it suffers from many drawbacks, such as complicated procedures and low yields.…”
Section: ■ Introductionmentioning
confidence: 99%
“…14,16 This thereby can lead to well-controlled and interesting self-rotational motions of the micromotors, which facilities many practical applications, such as cargo delivery and micropumping. 14,16 Although such a deposition method has been used to fabricate micromotors, it suffers from many drawbacks, such as complicated procedures and low yields. The development of simple and effective strategies to synthesize micromotors with distinct geometric and chemical symmetries is highly desirable, yet remains challenging.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation